Nucleation and growth of graphite in eutectic spheroidal cast iron: Modeling and testing - Carazo, Fernando Diego (2016)
A new model of graphite growth during the continuous cooling of eutectic spheroidal cast iron is presented in this paper. The model considers the nucleation and growth of graphite from pouring to room temperature. The microstructural model of solidification accounts for the eutectic as divorced and graphite growth rate as a function of carbon gradient at the liquid in contact with the graphite. In the solid state, the microstructural model takes into account three stages for graphite growth, namely: (i) from the end of solidification to the upper bound of stable eutectoid intercritical; (ii) during the stable eutectoid intercritical, and (iii) from the lower bound of stable eutectoid intercritical to room temperature. The micro and macrostructural models are coupled using a sequential multiscale approach. Numerical results for graphite fraction and size distribution are compared with experimental results obtained from a cylindrical cup, in which the graphite volumetric fraction and size distribution were obtained using the Schwarz-Saltykov approach. The agreements between the experimental and numerical results for the fraction of graphite and the size distribution of spheroids reveals the importance of numerical models in the prediction of the main aspects of graphite in spheroidal cast iron.